Impact of oral and mental health over the quality of life of older people in a Family Health Unit - Mariama Gentil MUSSOLIN; Luana Pinho de MESQUITA-LAGO; Maria Conceição Pereira SARAIVA; Soraya Fernandes MESTRINER (RGO: Revista Gaúcha de Odontologia, 2020)
ABSTRACT Objective This study sought to analyze the impact of oral and mental health on the quality of life of older people enrolled in a Family Health Unit, as well as its associated factors. Methods This was a cross-sectional, descriptive, exploratory study, conducted through interviews. The probabilistic sample consisted of 86 older people, users of the unit, aged 60 and over, dependent or independent, from both sexes. The methodological frameworks adopted for data collection were the evaluation of oral health conditions (edentulism) and the structured interview, employing oral health perception questionnaires (SB-Brazil), the OHIP – 14 (Oral Health Impact Profile), and the PHQ-2 (Patient Health Questionnaire – Two Items) screening tool for depressive disorders. Secondary data was collected from e-SUS individual records (e-SUS Primary Care). Results The majority of the sample (64%) was female, between 60 and 90 years old (mean of 72.4 years). Most frequently occurring OHIP-14 dimensions were pain (16.3%) and psychological disability (11.6%). The variables age, income, schooling, need for and use of prostheses, activities of daily living (ADL), self-reported diseases (diabetes, hypertension and cancer) had no significant association with quality of life measures related to oral health. A good correlation and association (p < 0.001) between PHQ-2 (depressive disorders) and OHIP-14 scores was observed. Conclusion In conclusion, an association between oral and mental health can be observed in older people; thus, for this population-especially in the case of older women oral and mental health care requires an extensive and multiprofessional approach, aimed at improving quality of life.